Sustained release of OIC-A006 from PLGA microspheres to induce osteogenesis of composite PLGA/β-TCP scaffolds - Lin Liulan; Dong Yangyang; Zhou Qi (Science and Engineering of Composite Materials, 2017)
In this article, poly(lactic-co-glycolic acid) (PLGA) microspheres containing the drug OIC-A006 were prepared by ice bath extraction and poly(lactic-co-glycolic acid)/ β-tricalcium phosphate (PLGA/β-TCP) scaffolds were prepared by freeze-drying. Three kinds of scaffold were prepared by adding no drug, direct loading the drug, and loading with drug microspheres. The mechanical strength, degradation, and microstructure of the scaffolds were analyzed. The drug delivery properties of the scaffolds were determined using high-performance liquid chromatography (HPLC). It was found that PLGA/β-TCP scaffolds with PLGA microspheres that contained the drug OIC-A006 exhibited a biphasic drug release pattern. Sustained release of the drug OIC-A006 was beneficial to cell adhesion and proliferation. Experiments on rats showed that composite PLGA/β-TCP scaffolds with PLGA microspheres containing the drug OIC-A006 produced good bone formation and bone induction.